2001
DOI: 10.1128/cdli.8.5.904-908.2001
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Assay for Measuring Toxoplasma gondii Immunoglobulin G Avidity

Abstract: A Toxoplasma gondii immunoglobulin G (IgG) avidity enzyme-linked immunosorbent assay (ELISA) was developed that combines the accuracy of assays based on end point titers and the relative ease of assays based on optical density values. Like published procedures, the new assay's avidity index (AI) was based on differential T. gondii-specific IgG reactivity in serum-treated wells washed with urea buffer versus that in wells washed with control buffer; unlike previous assays, however, the IgG reactivity was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…One study evaluated the IgG AI using single-dilution assays with and without urea and showed that because the signal obtained in an enzyme immunoassay system is not linear, it makes a difference whether the Toxoplasma IgG AI is calculated from the optical density values or from the activity of Toxoplasma-specific IgG antibodies measured in international units per ml (23).…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluated the IgG AI using single-dilution assays with and without urea and showed that because the signal obtained in an enzyme immunoassay system is not linear, it makes a difference whether the Toxoplasma IgG AI is calculated from the optical density values or from the activity of Toxoplasma-specific IgG antibodies measured in international units per ml (23).…”
Section: Discussionmentioning
confidence: 99%
“…This process introduces uncertainty, although experiments with only two dilutions showed excellent agreement with IgG avidity measurements obtained with four serial dilutions (13). Testing of a single dilution with and without urea was further evaluated by Prince and Wilson (21), who showed that because the signal obtained in an enzyme immunoassay system is not linear, it makes a difference whether the Toxoplasma-specific IgG avidity index is calculated from optical densities or activities measured in international units of Toxoplasma-specific IgG antibodies per milliliter (21).…”
Section: Discussionmentioning
confidence: 99%
“…Antibody avidities are used widely for discrimination between the acute and chronic phases of infectious diseases [13,14]. High-avidity autoantibodies against double-strand DNA are associated with renal damage in systemic lupus erythematosus [15], and high-affinity immune responses to insulin are associated with high risk for developing type 1 diabetes [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The ELISAs were performed as previously described [13][14][15][16], with modifications. Microtiter wells (Medisorp; Nunc, Roskilde, Denmark) were coated with recombinant DFS70 [9] or diphtheria toxoid (DT; List Biological Laboratories, Inc., Campbell, CA) in PBS (1 and 2 µg/ ml, respectively).…”
Section: Elisas For the Avidity Measurement Of Anti-dfs70 Autoantibodmentioning
confidence: 99%